Bangunan suci Sunda kuna - Munandar, Agus Aris. (Jagakarsa, Jakarta : Wedatama Widya Sastra, 2011)
Sacred places of Sundanese people in Jawa Barat.
ISBN 9789793256904 di kulit buku tidak sama dengan ISBN di title page
Includes bibliographical references (p. 143-149) and index.
Keywords: Sundanese (Indonesian people) -- Religion; Sacred space -- Indonesia -- Jawa Barat; Jawa Barat (Indonesia) -- Religion